Dietary intervention with green dwarf banana flour (Musa sp AAA) prevents intestinal inflammation in a trinitrobenzenesulfonic acid model of rat colitis - Scarminio, Viviane [UNESP]; Fruet, Andrea C. [UNESP]; Witaicenis, Aline [UNESP]; Rall, Vera L. M. [UNESP]; Di Stasi, Luiz C. [UNESP] (Pergamon-Elsevier B.V. Ltd, 2012)
Dietary products are among the therapeutic approaches used to modify intestinal microflora and to promote protective effects during the intestinal inflammatory process. Because the banana plant is rich in resistant starch, which is used by colonic microbiota for the anaerobic production of the short-chain fatty acids that serve as a major fuel source for colonocytes: first, green dwarf banana flour produces protective effects on the intestinal inflammation acting as a prebiotic and, second, combination of this dietary supplementation with prednisolone presents synergistic effects. For this, we used the trinitrobenzenesulphonic acid (TNBS) model of rat colitis. Our results revealed that the protective effect produced by a combination of 10% green dwarf banana flour with prednisolone was more pronounced than those promoted by a single administration of prednisolone or a diet containing 10% or 20% banana flour. This beneficial effect was associated with an improvement in the colonic oxidative status because the banana flour diet prevented the glutathione depletion and inhibited myeloperoxidase activity and lipid peroxidation. In addition, the intestinal anti-inflammatory activity was associated with an inhibition of alkaline phosphatase activity, a reduction in macroscopic and microscopic scores, and an extension of the lesions. In conclusion, the dietary use of the green dwarf banana flour constitutes an important dietary supplement and complementary medicine product to prevention and treatment of human inflammatory bowel disease. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Banana; Dietary products; Functional foods; Inflammatory bowel disease; Musa sp AAA; Ulcerative colitis; Trinitrobenzenesulfonic acid (TNBS); Rat